SOSIALISASI PEMANFAATAN HERBAL TOGA PADA PENYAKIT OSTEOARTHRITIS DI DESA GEDANGANAK, KEC. UNGARAN TIMUR, KAB SEMARANG - Yusuf, Yuzar Khasan; Putri, Fanisa Kurnia; Lestarini, Desak Ayu; Prihatiningrum, Gabby Zulya; Roni, Abdul; Suyudi, Salsabiela Dwiyudrisa (ABDI MAKARTI, 2025)
Osteoarthritis is a degenerative disease caused by joint cartilage damage, often resulting in pain and limited mobility. The high number of public complaints regarding joint pain serves as the background for this socialization activity. This activity aims to provide health awareness regarding the use of family medicinal plants TOGA as an alternative treatment for Osteoarthritis. The event was held in RT 02, RW 04, Mijen, Gedanganak Village, East Ungaran District, Semarang Regency, focusing on the utilization of turmeric, ginger, and lemongrass, which have natural anti-inflammatory and analgesic properties. The socialization method included lectures, interactive discussions, and an evaluation of participants' understanding through pre-tests and post-tests. A total of 13 participants attended the event, starting with a pre-test to measure their initial understanding of Osteoarthritis and the benefits of TOGA. After the educational session, participants took a post-test to assess their improved understanding. The evaluation results showed a significant increase, with the average pre-test score of 4,17 (41,67%). rising to 9.17 (91,67%) in the post-test. This data indicates that the socialization successfully enhanced participants' understanding of Osteoarthritis treatment using TOGA. Thus, the socialization of TOGA utilization has proven effective in increasing public knowledge about alternative Osteoarthritis treatments. It is hoped that the community can apply the use of herbal plants as a natural therapy in daily life. The sustainability of similar programs is highly needed to expand its benefits to a broader community.